Prevalence and Factors Associated with Postpartum Depression among Mothers Visiting Immunization Clinic at Birendranagar Municipality, Surkhet, Nepal - Adhikari, N.; Shrestha, B.; Chand, B.; Basel, P. (Kathmandu University Medical Journal, 2022)
Background Postpartum depression (PPD) is a disabling but treatable mental disorder that represents one of the most common complications of childbearing which can exert a wide range of effect on social, physical and mental health conditions of the mother and baby. Objective To identify the prevalence and factors associated with postpartum depression among mothers visiting immunization clinic at Birendranagar Municipality, Surkhet in year 2020. Method This study was a cross-sectional study. A total of 347 postpartum mothers were interviewed for data collection. Validated Nepali version of Edinburg Postnatal Depression Scale (EPDS) was used to identify postpartum depression. These mothers were permanent resident of Birendranagar who had delivered their babies in municipal hospital. Analysis was done using SPSS version 21.0. Chi square test was applied to identify association of postpartum depression with major interest of variables namely parity of mother, sex of a baby and recent planned or unplanned pregnancy. Odds ratio (OR) was calculated with 95% Confidence Interval (CI). Result The prevalence of postpartum depression was found to be 32.9% (27.9%, 37.8%). Several factors which were significantly associated with postpartum depression were; sex of the baby, history of abortion and recent pregnancy planned or unplanned. Conclusion Nearly one-third of postpartum mothers had depression. Hence screening of mothers for depression is of prime importance throughout the continuum of care. Likewise, the factors identified for postpartum depression needs to be taken care of well in advance for healthy mother and a baby.